Support needs around the time of diagnosis of parents caring for an infant with visual impairment or blindness in Denmark: a qualitative study. Issue 2 (21st February 2023) - Milde, Nina; Rasmussen, Annette; Nissen, Kamilla; Kessel, Line
Abstract : Objective: The whole family is affected when an infant is diagnosed with visual impairment or blindness. We aimed to describe the support needs of parents around the time of diagnosis. Design: We used a descriptive qualitative method based on the theory of critical psychology and conducted five semistructured interviews with a total of eight parents of children under the age of 2 years who had been diagnosed with blindness or visual impairment before the age of 1 year. Thematic analysis was used to extract primary themes. Setting: The study was initiated by a tertiary hospital centre specialised in the ophthalmic management of children and adults with visual impairment. Participants: Eight parents representing five families caring for a child under the age of 2 years with visual impairment or blindness participated in the study. The parents were recruited from the Department of Ophthalmology at Rigshospitalet, Denmark in relation to appointments in the clinic or by phone or email. Results: We identified three themes: (1) recognition and reactions during the time of diagnosis; (2) family, network and struggles; and (3) interaction with healthcare professionals. Conclusion: The main lesson for healthcare professionals is to bring hope at a time when all hope may seem to be lost. Second, a need to direct attention to families with no or sparse supportive networks. Third, coordinating appointments between hospital departments and at-home therapies and reducing the number of appointments to allow parents time to establish a family relation with their child. Parents respond well to competent healthcare professionals who keep them informed and who see their child as an individual rather than as a diagnosis.